SISTEM INFORMASI PPDB ONLINE DI YAYASAN PENDIDIKAN CENDANA RIAU - Moch Alfi Wahyudi Hakim; Isjoni Isjoni; Azhar Azhar (Universitas Riau, 2022)
SMA Cendana Pekanbaru is a school under the auspices of the Riau Cendana Education Foundation. It is one of the private schools that implements an online student admission system. The New Student Admissions Information System (PPDB) is able to provide support for the management through an online system. It makes the storage media integrated so that administrative data can be searched quickly, precisely, and accurately. It avoids the possibility of data misinformation. This study aims to analyze and describe the implementation of the PPDB Online system and the supporting factors for the online PPDB system at SMA Cendana Pekanbaru. The type of this research is descriptive qualitative, with data collection techniques and procedures consisting of documentation, observation, and interview. From the research, it can be found that there are almost no significant obstacles to implementing the system at SMA Cendana Pekanbaru. The main factors supporting the implementation are the principal's leadership, human resources, strategy and technology resources, and cost resources.